A guide to John Henry Newman : his life and thought - Vélez, Juan R. (The Catholic University of America Press, 2022)
"Provides a wide range of subjects on the life and thought of John Henry Newman (1801-1890), an Anglican clergyman, author, and poet who became a Roman Catholic priest, cardinal, and saint. The contributors come from disciplines such as theology, education, literature, history, and philosophy, highlighting the wide range of Newman's work"--